2015
DOI: 10.3109/13880209.2015.1027778
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activities ofWithania somnifera: Current research, formulations, and future perspectives

Abstract: Context: Cancer, being a cause of death for major fraction of population worldwide, is one of the most studied diseases and is being investigated for the development of new technologies and more accurate therapies. Still the currently available therapies for cancer have many lacunae which affect the patient's health severely in the form of side effects. The natural drugs obtained from the medicinal plants provide a better alternative to fight against this devastating disease. Withania somnifera L. Dunal (Solan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 59 publications
(66 reference statements)
0
74
0
Order By: Relevance
“…Ashwaganda has beneficial effects on diseases of cardiovascular nature (Ravindran et al, 2015a), obesity, diabetes, infection, cancer (Choi and Kim, 2015, Khazal et al, 2014, Rai et al, 2016), arthritis (Gupta and Singh, 2014, Khan et al, 2015) and gastric inflammation (Kim et al, 2016). The major constituent in Ashwaganda, identified as Withaferin A, itself is an inhibitor of HMG-CoA, angiotensinogen-converting enzyme, (Ravindran et al, 2015b) can lower total cholesterol, triglycerides, higher HDL/LDL ratios (Shukla et al, 2014) and reduce severity or incidence of myocardial infarction, (Khalil et al, 2015) stroke (Ahmad et al, 2015, Raghavan and Shah, 2015, Sood et al, 2015) and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Ashwaganda has beneficial effects on diseases of cardiovascular nature (Ravindran et al, 2015a), obesity, diabetes, infection, cancer (Choi and Kim, 2015, Khazal et al, 2014, Rai et al, 2016), arthritis (Gupta and Singh, 2014, Khan et al, 2015) and gastric inflammation (Kim et al, 2016). The major constituent in Ashwaganda, identified as Withaferin A, itself is an inhibitor of HMG-CoA, angiotensinogen-converting enzyme, (Ravindran et al, 2015b) can lower total cholesterol, triglycerides, higher HDL/LDL ratios (Shukla et al, 2014) and reduce severity or incidence of myocardial infarction, (Khalil et al, 2015) stroke (Ahmad et al, 2015, Raghavan and Shah, 2015, Sood et al, 2015) and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in different forms of drug preparation from ancient time to improve the human longevity and vitality (Kulkarni & Dhir, ; Sangwan et al, ). Recent pharmacological studies have revealed that W. somnifera possess innumerable pharmacological actions including anti‐inflammatory (Chandra, Chatterjee, Dey, & Bhattacharya, ), antioxidant (Dhanani, Shah, Gajbhiye, & Kumar, ), antihypertensive (Andallu & Radhika, ), neuroprotective (Ahmad et al, ), immune modulation (Agarwal, Diwanay, Patki, & Patwardhan, ), anticancer (Jayaprakasam, Zhang, Seeram, & Nair, ; Rai, Jogee, Agarkar, & CAd, ) activities and also help in improvement of stress‐related disorders (Archana & Namasivayam, ). The therapeutic potential of W. somnifera is mainly due to the presence of various active moieties having a steroidal lactone ring in their structure called Withanolide (22‐hydroxyergostan‐26‐oic acid‐26,22‐lactone) (Mirjalili, Moyano, Bonfill, Cusido, & Palazón, ).…”
Section: Introductionmentioning
confidence: 99%
“…Withaferin A (WA), one of the steroidal lactones, is a bioactive constituent of the Indian herb Withania somnifera (commonly known as Ashwagandha or Indian winter cherry), a wild plant that is widely distributed across the South Asian field, and is a traditional medicine for various diseases, such as inflammatory diseases, autoimmune diseases and malignant tumors …”
mentioning
confidence: 99%
“…Withaferin A (WA), one of the steroidal lactones, is a bioactive constituent of the Indian herb Withania somnifera (commonly known as Ashwagandha or Indian winter cherry), a wild plant that is widely distributed across the South Asian field, (3,4) and is a traditional medicine for various diseases, such as inflammatory diseases, autoimmune diseases and malignant tumors. (5) The anticancer activity of WA was reported for the first time in 1967 (6) and several investigations have since been performed to determine its potential as an anticancer agent. Previous reports have demonstrated that WA affects microtubules or vimentin intermediate filaments and, subsequently, exerts cytotoxicity or inhibition of the epithelial-mesenchymal transition.…”
mentioning
confidence: 99%